Scientific digital poster assignments: strengthen concepts, train creativity, and communication skills - Wisanti Wisanti; Novita Kartika Indah; Eva Kristinawati Putri (International Journal of Evaluation and Research in Education (IJERE), 2024)
Student-centered learning promotes the development of students’ knowledge and skills with poster assignments used to ensure their active participation in academics. Therefore, this research aims to explore student competencies in concept strengthening, creativity, and communication skills from working on digital poster project assignments. Research using observation method with a quantitative approach. Data were collected from 86 participants learning plant systematics in their first semester based on the criteria for strengthening the concept, creativity, communication, and student responses. The instruments used for data collection were a poster scoring rubric and a closed questionnaire. Data were analyzed descriptively with simple statistics in the form of average, standard deviation, and percentage. The hypothesis about the correlation of concept strengthening, creativity, and communication was tested with Spearman’s coefficient. The result showed that students made 29 posters with concept strengthening, creativity and communication skills in the very good (3.42±0.49), very good (3.57±0.26), and very good (3.41±0.25) categories, respectively. Student competency shows a positive correlation between communication skills and concept reinforcement and between communication skills and creativity. Students give a positive response to the application of posters in learning in terms of learning experiences, concept strengthening, creativity and communication. Hence, using posters as project assignments in learning helps develop students’ knowledge and skills by acquiring varied experiences.